Pelatihan dan Pendampingan Aplikasi Keuangan BukuWarung pada Home Industry Katering Big Alind di Kelurahan Sendangadi - Febianita Ayu Larassati; Hasim As’ari (Universitas Muhammadiyah Manado, 2023)
Community Service activities are carried out to provide assistance and training on the importance of accounting and financial reports to determine company performance in terms of finance by utilizing current technological advances. The service activity was carried out at the Big Alind catering home industry in Sendangadi Village, Mlati District, Sleman Regency. The reason for the service was due to the lack of competence of the business owner in bookkeeping reports in the business being run. The method used in this activity is the method of mentoring and direct training in preparing financial reports using the BukuWarung application for business owner. Considered successful when business owner are able to understand the differences before and after being given assistance and training. From the results of the service activity, business owner understand the importance of making structured financial reports, by utilizing the BukuWarung financial application and also the understanding of business owner regarding financial reports that will be prepared in the following year.